Gustav Gloom and the Inn of Shadows - Castro, Adam-Troy (Castro, Adam-Troy. Gustav Gloom, 2015)
"Gustav and Fernie's adventures in the Dark Country continue as they search for their families. But as they get closer to discovering their families' fates, their mission is once again threatened by old foes--as well as some new, even more treacherous, ones. Will Gustav and Fernie be able to battle their way through and rescue their families before it's too late?" --